Molecular Diversity of Candida albicans Isolated from Immuno-compromised Patients, Based on MLST Method - Seyed Mohammad Hosein AFSARIAN; Hamid BADALI; Tahereh SHOKOHI; Sohrab NAJAFIPOUR (Tehran University of Medical Sciences, 2015)
Background: As regards multilocus sequence typing (MLST) method directly analyze the polymorphism within DNA sequences; we performed the first nationwide study on the genotypic relationships of Candida albicans strains obtained from oropharynx and bronchoalveolar lavage (BAL) samples from immunocompromised patients. Methods: Fourteen epidemiologically unrelated clinical strains of C. albicans were obtained from three hospitals in Mazandaran Province, Iran (2006 to 2012) from seven patients with pulmonary infections and the rest with oropharyngeal samples of immunocompromised patients. Seven loci of housekeeping genes were sequenced for all fourteen isolates. Results: MLST was applied to a subset of 14 unrelated isolates. Seventy-one (2.5%) nucleotide sites were found to be variable. Accordingly, 60 different alleles were identified in seven loci among the isolates, among which two new alleles were obtained. Furthermore, 12 independent diploid sequence types (DSTs) including five novel DSTs were identified. The fourteen unrelated isolates were placed in 10 clonal clusters (CC) while two isolates were singletons, by eBURST analysis. Most of the isolates belonged to CC461 of eBURST analysis from the clade 11 and two isolates assigned to CC172 from the clade 15. Conclusion: Pathogen distribution and relatedness for determining the epidemiology of nosocomial infections is highly recommended for pathogen control methods.